Effectiveness of the Eggs Make Kids demand‐creation campaign at improving household availability of eggs and egg consumption by young children in Nigeria: A quasi‐experimental study. Issue 1 (8th November 2022) - Larson, Leila M.; Frongillo, Edward A.; Kase, Bezawit E.; Neufeld, Lynnette M.; Gonzalez, Wendy; Erhabor, Irowa; Djimeu, Eric W.
Abstract: Using a quasi‐experimental design, our study aimed to determine the effectiveness of the 'Eggs Make Kids Sharp & Bright and Strong & Active' demand‐creation campaign in Nigeria. The intervention arm received emotionally compelling radio and television advertisements about eggs, and was exposed to promotional activities and advertising about eggs at points of purchase, schools and health facilities; the comparison arm received no intervention. Children 6–59 months of age (intervention: n  = 1359; comparison: n  = 1485) were assessed 14 months apart. Intent‐to‐treat analyses with analysis of covariance method assessed the impact of the intervention on caregivers' behaviour towards eggs, caregivers' willingness to pay for eggs, availability of eggs in households, and consumption of eggs by children 6–59 months of age. Analyses were adjusted for possible confounders and perceived effects of COVID‐19 on finances and food consumption. Compared to the comparison arm, the intervention arm showed a greater prevalence of household egg acquisition (odds ratio = 1.34, p  < 0.0001), and larger improvements in caregiver self‐efficacy ( β  = 0.242, p  = 0.004) and intent to feed eggs to children ( β  = 0.080, p  = 0.021). No effects were found on children's egg consumption or caregivers' reported willingness to pay for eggs. The lack of impact on child egg consumption despite increased acquisition of eggs and caregiver self‐efficacy suggests that other barriers to child consumption may exist. Additional research should further investigate factors that may influence intrahousehold distribution of eggs and whether these may also influence other nutritious foods. Abstract : Key messages: An emotionally engaged demand creation campaign around eggs resulted in small improvements in household acquisition of eggs and caregivers' self‐efficacy and intent to feed eggs to their child 6–59 months of age, but did not improve egg consumption in children. Economic hardships imposed by the COVID‐19 pandemic and low interpersonal communication associated with the campaign may have contributed to the lack of effects of egg consumption. Demand generation activities as stand‐alone activities are insufficient in improving egg consumption among children 6–59 months of age in this context.